2020
DOI: 10.3390/microorganisms8111664
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Microbiome in the Small Intestine of Hooded Seals (Cystophora cristata)

Abstract: Arctic hooded seals (Cystophora cristata) are monogastric carnivores that go through extreme fasting and re-feeding in early life. They are born isolated on sea ice; suckle high-fat milk for four days and may then fast for up to one month before they start hunting and feeding on small prey (fish and crustaceans). Previous studies of the gut microbiota in pinnipeds have focused on the large intestine, while little data exist on the small intestinal microbiota. In this study, the bacterial microbiome in the prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Indeed, the sucking lice of pinnipeds represent an interesting system in which to study the variation in microbiome composition and the drivers of this variation at an intraspecific level because: (1) these lice have well defined, isolated populations (infrapopulations) on individual seal hosts, due to an expected low rate of horizontal dispersal among host individuals, which is only possible during the seals' haul-out periods on land or ice (Kim, 1985;Leonardi et al, 2013Leonardi et al, , 2019; and (2) these lice feed only upon the blood of their host (Snodgrass, 1944;Kim, 1985), so that it can be assumed that individuals from the same infrapopulation feed upon "exactly" the same resource (i.e., the blood of the individual seal on which they occur). In addition, previous studies conducted on seal microbiomes have found that while factors such as species identity, age, sex, and diet play a role in shaping seal microbial communities, seals show evidence of a core microbiome with which they have co-evolved (Nelson et al, 2013;Acquarone et al, 2020;Kim et al, 2020;Stoffel et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the sucking lice of pinnipeds represent an interesting system in which to study the variation in microbiome composition and the drivers of this variation at an intraspecific level because: (1) these lice have well defined, isolated populations (infrapopulations) on individual seal hosts, due to an expected low rate of horizontal dispersal among host individuals, which is only possible during the seals' haul-out periods on land or ice (Kim, 1985;Leonardi et al, 2013Leonardi et al, , 2019; and (2) these lice feed only upon the blood of their host (Snodgrass, 1944;Kim, 1985), so that it can be assumed that individuals from the same infrapopulation feed upon "exactly" the same resource (i.e., the blood of the individual seal on which they occur). In addition, previous studies conducted on seal microbiomes have found that while factors such as species identity, age, sex, and diet play a role in shaping seal microbial communities, seals show evidence of a core microbiome with which they have co-evolved (Nelson et al, 2013;Acquarone et al, 2020;Kim et al, 2020;Stoffel et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The GI bacterial communities in pinnipeds commonly appear to be composed of only a few phyla, such as Firmicutes, Bacteroidetes, Fusobacteria, and Proteobacteria ( Lavery et al, 2012 ; Smith et al, 2013 ; Delport et al, 2016 ; Numberger et al, 2016 ; Bai et al, 2021 ). Moreover, the consistent and frequent detections of these taxa in both pups and adults across studies ( Nelson et al, 2013 ; Smith et al, 2013 ; Tian et al, 2020 ) have prompted several authors to propose the existence of a common bacterial “ core ” ( Numberger et al, 2016 ; Pacheco-Sandoval et al, 2019 ; Acquarone, Salgado-Flores & Sundset, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the probable existence of a bacterial core in pinniped GI microbiomes, huge intra- and interspecific variations in bacterial taxa abundance have also been reported, the causes of which remain poorly understood although they are likely associated with both specific ecological and biological preferences as well as differences in methodological approaches among studies ( Milani et al, 2013 ; Acquarone, Salgado-Flores & Sundset, 2020 ). For example, diet-driven variations in bacterial microbiotas have been reported in several pinnipeds species and appear to be the principal factors that influence the overall bacterial composition ( Aurioles et al, 1984 ; Porras-Peters et al, 2008 ; Maslowski & Mackay, 2011 ; Delport et al, 2016 ; Masper et al, 2019 ; Pacheco-Sandoval et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Wildlife Microbiology 2.0” gathers twelve research papers related to the symbiotic gut microflora and bacterial pathogens in wildlife, and how these are affected by both natural and anthropogenic factors in their environment. This Special Issue includes studies of the oral microbial community of the micro-endemic and critically endangered admirable red-belly toad in southern Brazil [ 8 ], the gut microbiome of the invasive small Indian mongoose, a pervasive predator disrupting the native ecology in the Caribbean islands [ 9 ], the fecal microbiota of the Egyptian mongoose, a medium-size carnivore in Iberia, Europe [ 10 , 11 ], and the bacterial microbiome in the small intestine of hooded seals, a monogastric carnivore that goes through extreme fasting and re-feeding in early life [ 12 ]. The environment and wildlife species can also be reservoirs of human and animal pathogens and antibiotic resistance.…”
mentioning
confidence: 99%